ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) JASA LINGKUNGAN HIDROLOGI KAWASAN HUTAN PRODUKSI GUNUNG LOI-LOIYO (STUDI KASUS DESA LAROONAHA KECAMATAN OHEO KABUPATEN KONAWE UTARA) - Laode Midi; Safril Kasim; Saldin Saldin (Universitas Haluoleo, 2016)
Forest hydrological environmental service such as water resource was one of the most important environmental services produced by forest. The objective of this study is factors affected the society in determining the analyz economic valueof forest hydrological environmental service. This research used Willingness to Pay (WTP) method as appreciation of Laroonaha community village to the hydrological environmental services of productive forest area surrounding. Besides, Multiple Regressions method used to determine the main factor influenced the community in deciding the economic value.The result of this research showed that the total of water consumption yielding from productive forest area of Loi-loiyo Mountain by the Laroonaha society is 1.039,5 m3/month with an average usage about 14,4375 m3/KK/month or about 12.474 m3/year with an average usage of 173,25 m3/KK/year.The value of total WTP hydrological environmental services for the Laroonaha society was about Rp. 6.543.652/monthwith an average value of WTP about Rp. 6.295/KK/month. The main factor affected the respondents WTP value was the average of the respondent family income to determine on the confidence level of 99%, whereas the number of family member and the educational level was not significantly affected, with standard error 20% and 5%. Keywords: EconomicValuation, Hydrological Environmental Service,Willingness to Pay.